Effect of seed size and drying temperature on the hot air drying kinetics and quality of Chinese hickory (Carya cathayensis) storage. Issue 9 (19th July 2021) - He, Zhiping; Ye, Minqian; Zhang, Youqing; Wu, Fenghua; Fu, Maorun; Sun, Fei; Liu, Xingquan
Abstract: The development of an effective drying method to extend the shelf life of raw Chinese hickory ( Carya cathayensis) is a major postharvest processing in the nut industry. In this paper, the effect of seed size and drying temperature on hot air drying kinetics and quality of Chinese hickory were detected. Our results reveal that the seed size greatly affects the final equilibrium moisture content of Chinese hickory. So, we predict that a larger Chinese hickory must be dried at a higher temperature. An Arrhenius‐type relationship is found between effective diffusivity ( D eff ) of Chinese hickory and drying temperature where the activation energy is 40.85 kJ/mol. Accelerated storage results show that Chinese hickory drying at 35 and 45°C have lower acid values, peroxide values, higher content of unsaturated fatty acids than those of 55 and 65°C. We suggested that 45°C is a suitable temperature for the industrial‐scale drying of Chinese hickory. Practical applications: In China, the annual output of Chinese hickory is about 21, 500 metric tons. After harvest, fresh Chinese hickory is susceptible to decay and germinate during storage. Recently, the proportion of cracked Chinese hickory and kernel products is constantly rose in the market. So the requirements for the quality of raw materials are increased. Drying is the most critical step after harvest. Traditionally, the drying of Chinese hickory is performed in the presence of the natural sun. In rainy days, Chinese hickory often cannot be dried in time. Hot air drying is a common drying method in industry. However, limited reports are available on hot air drying and its effect on the product quality of Chinese hickory seeds. The results of this paper will help to establish an effective industrial‐scale drying method of Chinese hickory. In addition, the effect of seed size on hot air drying kinetics was also first investigated.